EXTENT OF THE USE OF CLINICAL SUPERVISION MODEL FOR TEACHING PRACTICE SUPERVISION IN IMO STATE UNIVERSITY, OWERRI (Isagoge - Journal of Humanities and Social Sciences, 2021)
The seeming decline in the quality of teachers in Nigeria necessitated this study. The study adopted the descriptive survey research design. Four research questions guided the study while three hypotheses were tested at 0.05 level of significance. The population of the study comprised 323 respondents made up of 240 final students and 83 lecturers in the seven Departments of the faculty of Education Imo State University, Owerri. The entire population was used for the study. A researcher developed questionnaire was the instrument used for data collection. The instrument was validated by three experts. The Cronbach’s alpha method was used to determine the internal consistency of the items and it yielded a reliability coefficient of 0.74. The researchers with the help of four research assistants distributed and successfully collected 298 copies of the questionnaire administered. The research questions were answered using the mean, while the hypotheses were tested using z-test at 0.05 level of significance. It was found among others that pre-observational techniques were used to a very low extent t in Imo state university Owerri for teaching practice supervision. Based on the findings of the study, it was recommended among others that conference, workshops and seminars should be organized for lecturers at Imo State University where various techniques of clinical supervision will be exposed to them towards ensuring qualitative teaching practice supervision.